Asia, The Fourth Transformation and the Global Change of Power (2020)
This paper mainly places Mexico’s national interests within its foreign policy, as part of the transformation context that Mexico is currently undergoing, known as The Fourth Transformation –4T. It takes into account changes in the global balance of power and presents alternatives in this area, which will contribute to their accomplishment. Based on the importance of diversifying international economic trade relationships, as a key factor to eliminate dependence on the North American market, Mexican exports to the American market accounted for 76% of the total exports in 2018 according to the Secretariat of Economy (2019). Consequently, this paper is based on the assumption that “while the country’s political and economic diversification is necessary, there are still no clear strategies, as opposed to the proposals made by our main partners in the world, especially those in Asia (China, South Korea, and Japan), which have recently shown interest in strengthening their ties with Mexico.” To this end, an analysis is conducted using the neorealist approach of international relationships, of the sources of power by Joseph S. Nye Jr. (2011), and of the power transition theory by Tammen (2000).